Pengaruh Ekstrak Etanol Daun Tampa Badak (Voacanga foetida (Bl.) K Schum) Terhadap Klirens Kreatinin Mencit Putih (Mus musculus L.) Jantan - Susanty, Adriani; Sandi, Nofri Hendri; M, Wewen Sista (Jurnal Penelitian Farmasi Indonesia, 2013)
A research on effect of ethanol extract of tampa badak (Voacanga foetida) to renal function of male white mice at doses 100, 200 and300mg/kgBW of weight has been studied. The employed parameter was measuring creatinine clearence and the kidney weight ratio of malewhite mice in the 61st day. In this study, four group of male white mice, each of which consisted of five mice, were utilized. Three groups weregiven suspension of ethanol extract of tampa badak and the other group as a control was simply given suspension of NaCMC 1% orally. Themeasurement method used was the method of chemical reaction with using reagent Diasys and by using ultraviolet-visible spectrophotometry(Microlab 200) at wavelength 505 nm. The result showed that application of ethanol extract of tampa badak did not give significant effect(p>0,05) to 24 hour urine volume, urinary creatinie quantity, serum creatinine, cretinine clearance as well as kidney weight ratio of malewhite mice.